2013
DOI: 10.1111/1556-4029.12304
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Digital Radiography, Computed Tomography, and Magnetic Resonance in the Detection of Gunshot Residues in Burnt Tissues and Bone

Abstract: The radiological search for GSR is crucial in burnt material although it has been rarely tested. In this study, thirty-one bovine ribs were shot at near-contact range and burnt to calcination in an oven simulating a real combustion. Computed tomography (CT) and magnetic resonance (MR) were performed before and after carbonization and compared with former analyses with DR (digital radiography); thus comparing the assistance, the radiological methods can provide in the search for GSR in fresh and burnt bone. DR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Fresh clean bone was chosen instead of bone covered with soft tissue because of fear that subsequent removal of soft tissue could somehow modify any bone fragment displacement around the margin of the wound. In a previous radiological study performed on similar samples with a layer of skin or soft tissues, the presence of the detachment of some parts of the external circumference of the entrance wound could be observed. Thus, there is no indication that bone with soft tissue should behave differently from fresh bone in the case of contact wounds.…”
Section: Methodsmentioning
confidence: 83%
“…Fresh clean bone was chosen instead of bone covered with soft tissue because of fear that subsequent removal of soft tissue could somehow modify any bone fragment displacement around the margin of the wound. In a previous radiological study performed on similar samples with a layer of skin or soft tissues, the presence of the detachment of some parts of the external circumference of the entrance wound could be observed. Thus, there is no indication that bone with soft tissue should behave differently from fresh bone in the case of contact wounds.…”
Section: Methodsmentioning
confidence: 83%
“…Postmortem imaging analysis, including X-ray and computed tomography (CT), has been used to not only identify retained bullets in penetrating gunshot wounds but as an adjunctive technique to gross inspection for the determination of entrance versus exit gunshot wounds and for determining the wound pathway [11]. Comparative studies in bone have demonstrated the superiority of digital radiography versus CT and magnetic resonance imaging in detecting metallic gunshot residue particles from both fresh and cremated bone [12]. These radiodense deposits also persist through intermediate Other ancillary techniques that may be used to address the presence of bullet wipe from gunshot wounds include biochemical tests, methods involving atomic absorption spectroscopy (AAS), neutron activation analysis (NAA), inductively coupled plasma-atomic emission spectroscopy (ICP-AES), proton-induced X-ray emission (PIXE), and scanning electron microscopy coupled with an energy dispersive X-ray analyzer (SEM-EDX).…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem imaging analysis, including X‐ray and computed tomography (CT), has been used to not only identify retained bullets in penetrating gunshot wounds but as an adjunctive technique to gross inspection for the determination of entrance versus exit gunshot wounds and for determining the wound pathway [11]. Comparative studies in bone have demonstrated the superiority of digital radiography versus CT and magnetic resonance imaging in detecting metallic gunshot residue particles from both fresh and cremated bone [12]. These radiodense deposits also persist through intermediate targets, as shown by an experimental model utilizing porcine skin wherein X‐ray analysis detected radiodense fragments on soft tissues from partial jacket rifle rounds at distances of 6 m through an intermediate wooden target of 5 cm thickness [13].…”
Section: Discussionmentioning
confidence: 99%
“…The method is to use a single X-ray source, X-ray sensor and computer platform, which together, in general, will allow you to calculate the mineral density of the bone (Jimenez-Mendoza et al, 2011). Known methods of computed tomography, digital radiography, and magnetic resonance are sufficiently sensitive to study bone residual material and to determine the causes of death of animals (Amadasi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%